Manajemen Tenaga Kependidikan di Madrasah Aliyah - Dinta Hafidzi; Olianda Adistiana; Fahruruzi Ahmad Thobi’i (Al-Misbah (Jurnal Islamic Studies), 2019)
Education staff management is an activity to manage every individual who is in the Education environment in carrying out their respective duties and functions to run more effectively. The success of school / madrasah-based management is largely determined by its leaders in managing the teaching staff available at school / madrasas. The school principal has responsibility tasks related to the management of the teaching staff which is not an easy task. In addition to striving to achieve the goals of the school but also striving to achieve the goals of educational staff (teachers and employees) in person. From the field of Administration whose role is very important in the world of education. In MAN 3 BANTUL there is an activity that is related to administration which is modern, systematic and makes it easy for all parties. At this school they use a one door service, in which all other information and administrative services become very clear and valid. And this service is placed in the front of the school environment after the entrance gate and in the lobby in order to facilitate and make it a strategic place.